Avaliação dos processos GMAW com transferência por curto-circuito convencional e controlado (STT) aplicados na soldagem circunferencial mecanizada - Nascimento, Lucas Alves do (2015)
The large Brazilian territory and the increasing demand for oil and gas consumption created a national challenge for the fast and reliable expansion of pipelines. The need for construction and maintenance and of new pipelines require welding processes with high productivity, reliable, that produce quality welds, to the detriment of the coated electrode process, currently the most used in the pipe union. Therefore, this work presents the study of girth welding of carbon steel pipes (API 5L, 2012) with 8\" nominal diameter and 8.0 mm thickness. The welds were carried out in downhill progression by using orbital displacement device (mechanized welding), ER70S-6 wire with 1.2 mm diameter and Ar+25%CO2, as shielding gas. The material was deposited on butt V joint with 15º bevel, 1 mm of root face and 3 mm root opening, without backing. For the proposed joint, GMAW processes with short-circuit metal transfer were assessed in both conventional and derivative modes by using commercial power source namely STT (Surface Tension Transfer). In this context, welding parameters were investigated for root pass and filling pass. The analysis were obtained from visual inspection and mechanical tests (uniaxial tensile test, root and face bending, nick-break, charpy V-notch impact test, macrography test and hardness profile) with objective to qualify both processes. In addition to the qualification of welding processes, it was also necessary to make improvements in the experimental rig, the test-pipe assembly and the existing electronic system. Among such improvements, it was carried optimization the trigger synchronism between the power source, the data acquisition system and the orbital machine; the elimination of equipment shutdown during welding; the optimization of automatic adjustment control of the contact tip to workpiece distance (DBCP) and the elimination of visual narrowing of the heat zone caused by fixtures. Pre-tests were carried to qualitatively evaluate the temperature decay on both sides of the welded joints motivated by the excessive frequency of defects (lack of side fusion) previously observed. The results showed that the temperature decay rate on one side of the pipeline does not affect the welding. Finally, only the derivative process (STT) was capable to obtain a robust set of parameters for the proposed joint, in accordance to the acceptability criteria of standard API 1104 (2010). On the other hand, the conventional process GMAW was capable only to obtain a set of parameters for the root pass.